2023
DOI: 10.3847/1538-3881/acb5a2
|View full text |Cite
|
Sign up to set email alerts
|

TOI-4562b: A Highly Eccentric Temperate Jupiter Analog Orbiting a Young Field Star

Abstract: We report the discovery of TOI-4562b (TIC-349576261), a Jovian planet orbiting a young F7V-type star, younger than the Praesepe/Hyades clusters (<700 Myr). This planet stands out because of its unusually long orbital period for transiting planets with known masses (P orb = 225.11781 − 0.00022 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 152 publications
0
3
0
Order By: Relevance
“…In this paper we present the detection and validation of a transiting mini-Neptune (hereafter TOI 4633 c) orbiting a bright (Vmag = 9.0), nearby (d = 95 pc) G Dwarf, that was detected by citizen scientists. The period of 272 days makes this planet the second longest-period confirmed planet identified in the TESS data to date (with the longest being TOI 4600c, Mireles et al 2023), and only one of five confirmed TESS planets with orbital periods longer than 100 days (Dalba et al 2022;Heitzmann et al 2023). Furthermore, the long orbital period and incident flux of ∼1.6 F ⊕ places it in the habitable zone of its host star, making it only the fourth habitable zone planet identified in the TESS data to date, following TOI 700 d (Gilbert et al 2020;Rodriguez et al 2020), TOI 700 e (Gilbert et al 2023), and TOI 715 b (Dransfield et al 2024).…”
Section: Introductionmentioning
confidence: 80%
“…In this paper we present the detection and validation of a transiting mini-Neptune (hereafter TOI 4633 c) orbiting a bright (Vmag = 9.0), nearby (d = 95 pc) G Dwarf, that was detected by citizen scientists. The period of 272 days makes this planet the second longest-period confirmed planet identified in the TESS data to date (with the longest being TOI 4600c, Mireles et al 2023), and only one of five confirmed TESS planets with orbital periods longer than 100 days (Dalba et al 2022;Heitzmann et al 2023). Furthermore, the long orbital period and incident flux of ∼1.6 F ⊕ places it in the habitable zone of its host star, making it only the fourth habitable zone planet identified in the TESS data to date, following TOI 700 d (Gilbert et al 2020;Rodriguez et al 2020), TOI 700 e (Gilbert et al 2023), and TOI 715 b (Dransfield et al 2024).…”
Section: Introductionmentioning
confidence: 80%
“…TESS systematically covers the entire sky with ∼28 day "sectors." However, as the TESS mission continues, it has slowly but surely built up baselines and discovered long-period planets akin to those spotted by Kepler (e.g., Kostov et al 2021;Dalba et al 2022a;Heitzmann et al 2023;Mann et al 2023;Mireles et al 2023;Orell-Miquel et al 2023) but orbiting far brighter host stars.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the NASA Exoplanet Archive reports only 27 confirmed TESS exoplanets with 10 < P < 100 days and a confirmed mass 0.25 < M J < 13. 36 Of TESS exoplanets with P > 100 days, only four have been confirmed (Kostov et al 2021;Dalba et al 2022;Heitzmann et al 2023;Mireles et al 2023). Since the TESS pipeline relies on observing repeated transits for detection, the majority of TOIs are not single transits.…”
Section: Introductionmentioning
confidence: 99%